Practical data communications for instrumentation and control - Park, John, 1953- (Practical professional books from Elsevier., 2003)
Instrumentation and control systems are highly reliant on data communications, so a working knowledge of the latest communications technologies and the essential protocols is essential for anyone designing, specifying or using instrumentation and control systems. This book is the only title on the market designed specifically for this audience. This is a comprehensive treatment of industrial data communication systems. Commencing with a thorough discussion of the popular RS-232, RS-422 and RS-485 standards it then moves on to industrial protocols, industrial networks and the communication requirements for the 'smart' instrumentation which is becoming de rigeur in industry today. The book also provides a solid grounding in the various Fieldbus and DeviceNet standards on the market today. This book provides you with the knowledge to analyse, specify and debug data communications systems in the instrumentation and control environment. *The essential guide to communications techologies and protocols for engineers designing, specifying or using instrumentation and control systems *Provides the knowledge required to analyze, specify and debug data communication systems, introducing the latest digital technologies *Coverage includes RS-232, RS422 and RS-485 standards, industrial networks and protocols, smart instrumentation, FieldBus and DeviceNet standards.